THE EFFECT OF QUALITY SERVICES AND FACILITIES ON STUDENT SATISFACTION - Uswah USWAH; Euis EVICASARI; Tuti SUGIARTI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2019)
In principle, prioritizing stakeholders’ satisfaction is the philosophy of all educational institutions including Sekolah Tinggi Farmasi Muhammadiyah located in Tangerang Banten. Quality services in high education are services that can meet the needs of students and their expectations. Thus, this study aims to determine the effect of service quality (reliability, responsiveness, empathy, guarantee, direct evidence (physical evidence) on the satisfaction of students who use services and facilities. In addition, this study also aims to determine the most influential dimensions of service quality in providing satisfaction to students. The samples were 24 people from all population of 460 students, where the research data was collected through questionnaires. Validity instruments were tested using the construct validity test and reliability instruments were tested using the Cronbach Alpha. SPSS Statistics 24.00 was employed to analyze frequency statistics. Hypothesis results that have been tested on the frequency table are 95% internal evidence evidence (a-5%). The results of the study show that the dimensions of reliability, responsiveness, assurance, empathy, and tangible have a positive effect on student satisfaction.